Teaching About Peace Through Children’s Literature - Steiner, Stan (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
Historically children’s literature has always been used as a teaching tool with children, but today the choices of literature has grown and the audience expanded. Teaching moral messages was an underlying foundation for making books available for children. Early children’s books were often tied to religious teachings and folklore that had implied messages of staying close to home, listening to elders, caring for others over oneself, and traditional gender roles to name a few. Many adults have identified other subliminal messages as they critically analyzed some of the literature from the past. Some messages you will find are passive women needing to be rescued by a courageous prince (Rapunzel, Sleeping Beauty), distrust of stepmothers or strangers (Hansel & Gretel, Cinderella), and ethnic stereotyping (Five Chinese Brothers, Little Black Sambo). As a result, adults have become more critical of the literature selected for children. Educators are expected to be more aware of stereotypes touching on ethnicity, gender, social status, religion and cultural identity. At the same time we must ask how much is too much or not enough when it comes to cultural sensitivity or more specifically, social consciousness?